PENGUATAN PENDIDIKAN KARAKTER PADA MATA KULIAH WAJIB KURIKULUM (MKWK) DI UNIVERSITAS NEGERI MAKASSAR - Mustari Mustari; Hadyan Hashfi MS (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This study aims to determine the strategy for implementing MKWK lectures to support strengthening character education at Makassar State University. The type and approach of this research is descriptive with a qualitative approach. The data collection technique is a questionnaire/questionnaire.The results of the study indicate that students who participate in MKWK generally know and understand that MKWK is a course that functions to shape dignified student character and civility, knowing the nature of MKWK is a course that strengthens students' spiritual commitment. In general, the respondents stated that the information was obtained from MKWK lecturers. Related to the character values that will be achieved by MKWK. Regarding the lecture strategy by MKWK lecturers, respondents also stated that the lecturer used the discussion and question and answer method, as well as problem solving case studies associated with strengthening character education. MKWK lecturers in the lecture process have developed intellectual (thought) aesthetic (taste), ethics and spiritual (heart), in developing and implementing teaching materials by integrating and connecting real life as part of the cash method, taking into account the problem of local wisdom. MKWK lecturers in terms of delivering character values, in this case smart, honest, caring, tough and academic culture are also the focus of attention in the process of implementing lectures.